Legal Recognition and Evidentiary Issues in Indonesia’s Digital Framework (Lembaga Contrarius Indonesia, 2026)
This study examines the epistemological and normative tensions between public truth and legal truth in the context of digital contracts in Indonesia. Public truth emerges from collective perceptions shaped by social media opinions, news narratives, and online justice movements. In contrast, legal truth derives from formal juridical processes that prioritize the validity of electronic signatures, contractual clauses, and evidentiary mechanisms in court. This divergence undermines the legitimacy of digital contracts, particularly when public discourse deems them unfair despite their legal validity. Existing research on digital contracts predominantly addresses legal validity and certainty, neglecting the epistemological dimensions of truth production and contestation. This study addresses that gap through normative juridical methods, employing qualitative analysis to interrogate disputes between contractual legality and online public opinion. The result reveal that tensions between public and legal truth erode public trust in the legal protections afforded by digital contracts. To mitigate this, regulatory transparency, enhanced digital law literacy, and responsive judicial dispute resolution mechanisms are essential. These insights underscore the urgent need to reconstruct the legitimacy of digital contracts in Indonesia, while offering a framework for comparative analysis in other jurisdictions facing analogous challenges.